Three Ribosomal Operons of Escherichia coli Contain Genes Encoding Small RNAs That Interact With Hfq and CsrA in vitro - Stenum, Thomas Søndergaard; Kongstad, Mette; Holmqvist, Erik; Kallipolitis, Birgitte; Svenningsen, Sine Lo; Sørensen, Michael Askvad (Frontiers in Microbiology, 2021)
Three out of the seven ribosomal RNA operons in Escherichia coli end in dual terminator structures. Between the two terminators of each operon is a short sequence that we report here to be an sRNA gene, transcribed as part of the ribosomal RNA primary transcript by read-through of the first terminator.The sRNA genes (rrA, rrB and rrF) from the three operons (rrnA, rrnB and rrnD) are more than 98% identical, and pull-down experiments show that their transcripts interact with Hfq and CsrA. Deletion of rrA, B, F, as well as overexpression of rrB, only modestly affect known CsrA-regulated phenotypes like biofilm formation, pgaA translation and glgC translation, and the role of the sRNAs in vivo may not yet be fully understood. Since RrA, B, F are short-lived and transcribed along with the ribosomal RNA components, their concentration reflect growth-rate regulation at the ribosomal RNA promoters and they could function to fine-tune other growth-phase-dependent processes in the cell. The primary and secondary structure of these small RNAs are conserved among species belonging to different genera of Enterobacteriales.